Chamaespartium Adans. (Leguminosae): a new record for the flora of Turkey - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2009)
Chamaespartium sagittale (L.) P.E.Gibbs (Leguminosae) is a new record for the flora of Turkey with specimens collected from Yuvacik Dam (Kocaeli province, NW Turkey). Its description, distribution maps, and photos are given.
Keywords: Chamaespartium; Fabaceae; new record; Turkey